Estimasi Asupan Energi dan Protein Itik Kerinci Sistem Umbar Di Kabupaten Kerinci Provinsi Jambi - Adrizal, Adrizal; Nur, Hanafi; Yusrizal, Yusrizal; Manin, Fahmida; Rahayu, Pudji (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2009)
This study was aimed at estimating true metabolizable energy (TME) and crude protein (CP) intake of Kerinci Duck reared under scavenging system in Kerinci District, Province of Jambi. Twovillages (Koto Majidin [KM] and Semerap [SP]) were selected for the study where ducks were the most common livestock kept by farmers. Koto Majidin was located deed in the land, whereas Semerap was close to a natural lake. Geographically, these villages had the same climate and constituted paddyproducingareas where at the time of the study, these locations were inharvesting season. Five mature 7 to 9-month old ducks (1 male and 4 females) were selected from each location and killed late afternoon after being scavenged for 9.0 (KM) to 11.5 hours (Semerap) for gizzard sampling. The results showedthat based on proximate analysis of gizzard contents and corrections made on scavenging time, TME intake by ducks in KM was not different from that in SP (618 vs. 996 kcal/kg), but CP intake was less in KM (3.90 vs. 7.28; P ≤ 0.01). Relative weights of gizzards of ducks were comparable in the twolocations. Thus, difference in body weight (1,352 [KM] vs. 1,579 kg [SP]; P ≤ 0.01) was likely in part influenced by different absolute weight of gizzard (55.6 vs. 78.0 g; P ≤ 0.01) and its contents (10.60 vs. 18.03 g; P ≤ 0.01). Scavenged feeds, which were similar in both locations, composed of grits, paddy,snails, and other unidentified ingredients. This study suggested that ducks scavenged feed in KM and SP had not got sufficient energy and protein for optimum production. Under the presencecircumstances, at least additional 20 g of feed composing of energy and protein source is required to meetnutrient requirements of a duck.